EMOTIONAL INTELLIGENCE AND JOB SATISFACTION AMONG JOURNALISTS IN TAMIL NADU: AN EXPLORATORY STUDY - S., Rajesh Kumar (International Journal of Research -GRANTHAALAYAH, 2023)
This research paper delves into the intricacies of emotional intelligence (EQ) and its impact on job satisfaction among professional journalists in Tamil Nadu. Emotional intelligence, encompassing the ability to recognize, manage, and regulate emotions, plays a pivotal role in the journalism profession. This study aims to fill a notable research gap by investigating the emotional intelligence levels of journalists in Tamil Nadu and their implications on work-related stress, job satisfaction, and organizational commitment.